Low temperature microhardness of Xe-intercalated fullerite C60 - Fomenko, L.S.; Lubenets, S.V.; Natsik, V.D.; Cassidy, D.; Gadd, G.E.; Moricca, S.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The Vickers microhardness of Xe-intercalated polycrystalline fullerite C60 (Xex C60, x ≃ 0.35)is measured in a moderately low temperature range of 77 to 300 K. A high increase in the microhardnessof the material (by a factor of 2 to 3) as compared to that of pure C60 single crystals is observed. It is shown that the step-like anomaly in the temperature dependences of the microhardnessof pure C60 single crystals recorded under the orientational fcc-sc phase transition (Tc ≃ 260 K) isalso qualitatively retained for Xex C60, but its onset is shifted by 40 K towards lower temperatures and the step becomes less distinct and more smeared. This behavior of H̅V(T)correlates with x-ray diffraction data, the analysis of which revealed a considerable influence of xenon interstitial atoms on the peculiar features of fullerite thermal expansion due to orientational phase transitions (see the paper by A.I. Prokhvatilov et al. in this issue).